Situation Report: Romania, 21 October 1964 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Chinese Communiqué on Nuclear Explosion Published Special Message of Chinese Leaders Soviet-Romanian Agreement on Delivery of Power Equipment Long-Term Economic Agreement with Czechoslovakia Technical-Scientific Agreement with Bulgaria